A Case of Seronegative Pulmonary-renal Syndrome: Diagnostic and Therapeutic Challenge - Muharremi, S; Poposki, A; Kovaceska, V; Tozija, L; Petrushevska, G; Gerasimovska, B; Bexheti, B; Gjorgjievski, N; Janevski, Z; Saidi, M; Spasovska, A; Poposka, B; et al. (Scientific foundation Spiroski, 2021)
BACKGROUND: Pulmonary renal syndrome (PRS) is not a single entity but is caused by varied etiologies, including anti-neutrophil cytoplasmic antibody (ANCA), associated small vessel vasculitis (such as Wegener’s granulomatosis, microscopic polyangiitis, and Churg-Strauss vasculitis), Goodpasture’s syndrome, systemic lupus erythematosus, Henoch-Schonlein purpura, cryoglobulinemia, and rare causes such as druginduced vasculitis and subacute endocarditis. CASE REPORT: We report a case of a 51-year-old man who was referred to our hospital with a 2-month history of breathing difficulties, mild hemoptysis, and deteriorated renal function with a serum creatinine of 269 μmol/L. Serological testing was negative for anti-neutrophil cytoplasmic antibody (ANCA) and anti-glomerular basement membrane (GBM) antibody, and also all cultures, including blood and urine, remained negative. In the renal biopsy, not linear deposition of IgG along the GBM and crescents at varying stages with extracapillary glomerulonephritis emphasizes the possibility of a double-seronegative pulmonary renal syndrome. Regarding therapeutic dilemmas, on the 3rd day of hospitalization, we initiated immunosuppression with cyclophosphamide and corticosteroids as well as plasma exchange (5 treatments). Under immunosuppressive therapy and plasma exchange, the patient’s status continually improved; there was no pulmonary bleeding, but the serum creatinine remained high and renal function remained in stage 4 chronic kidney disease. Four weeks later, he was hospitalized again, and we faced a new therapeutic dilemma because of the rapid relapse during immunosuppressive therapy and renal function deterioration that required hemodialysis treatment. Despite repeatedly negative results for anti-GBM and ANCA, initial immunosuppressive therapy with plasma exchange (9 treatments) was included again. The patient was discharged 30 days after admission in a stable general condition, with the maintenance immunosuppressive therapy with mycophenolate mofetil and hemodialysis 3 times/week. After 24 months, we have received information from the hemodialysis center that he is on regular hemodialysis and that he is in good condition. CONCLUSION: We think that in this atypical case, intensive plasma exchange and immunosuppressive therapy are crucial in the early stage and maintenance therapy is necessary for vasculitis in remission. This reported case has important clinical implications because pulmonary-renal syndrome with negative ANCAs and anti-GBM antibodies is extremely rare and no treatment recommendations have been established yet.